REPRESENTASI PEMIKIRAN MARXISME DALAM FILM BIOGRAFI STUDI SEMIOTIKA JOHN FISKE MENGENAI PERTENTANGAN KELAS SOSIAL KARL MARX PADA FILM GURU BANGSA TJOKROAMINOTO - Aisyah Nurul Kusumastuti; Catur Nugroho (Universitas Bunda Mulia, 2017)
Film is an audio-visual language that always record the reality that grows and develops in the community, and then project it on the big screen. The film Guru Bangsa Tjokoraminoto is a biopic which tells the history of Tjokroaminoto’s struggle to against the Dutch government’s policy and to eliminate social inequality inside the society at that time. In this film tucks into a Marxist ideology that not all of the audience will aware of it. Therefore, researchers are interested to analyze the representation of this ideology in the film. The study, entitles